2020
DOI: 10.1186/s13071-020-04352-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of abiotic factors, habitat type and urban wildlife on the ecology of hard ticks (Acari: Ixodidae) in urban and peri-urban habitats

Abstract: Background Ticks are increasingly acknowledged as significant vectors for a wide array of pathogens in urban environments with reports of abundant tick populations in recreational areas. The study aims to contribute to a better knowledge of the abiotic and biotic factors which impact the ecology of hard ticks in urban and peri-urban habitats in Romania. Methods Questing ticks were collected by flagging in seven recreational locations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 65 publications
(82 reference statements)
3
20
0
1
Order By: Relevance
“…This was not related to bias in the selection algorithm but because of the availability and abundance of wildlife hosts and questing ticks when the collection was performed. A previous study we conducted in these seven recreational locations in Cluj-Napoca showed a higher abundance of ticks in the urban versus the peri-urban locations, linked to the abundance and diversity of local wildlife species, particularly hedgehogs (E. roumanicus) (Borşan et al, 2020). These findings may explain the more diverse TBPs community we detected in urban sites, further highlighting the importance of urban dwellers such as hedgehogs, rodents, and birds in the ecology of tick-borne diseases.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…This was not related to bias in the selection algorithm but because of the availability and abundance of wildlife hosts and questing ticks when the collection was performed. A previous study we conducted in these seven recreational locations in Cluj-Napoca showed a higher abundance of ticks in the urban versus the peri-urban locations, linked to the abundance and diversity of local wildlife species, particularly hedgehogs (E. roumanicus) (Borşan et al, 2020). These findings may explain the more diverse TBPs community we detected in urban sites, further highlighting the importance of urban dwellers such as hedgehogs, rodents, and birds in the ecology of tick-borne diseases.…”
Section: Discussionsupporting
confidence: 52%
“…During the necropsy, the heart, liver tissue, and two skin biopsies (one from the interscapular region and the second from the ear pavilion that were pooled together for DNA isolation) were collected from each animal. All the tissue samples were labeled accordingly and stored at −20 • C. During the anesthesia -protocol described in Borşan et al (2020), 0.5 ml of blood were collected from the jugular or saphenous vein of eight hedgehogs. Blood sampling was unsuccessful in the case of three hedgehogs.…”
Section: Urban Wildlife Hostsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, H.punctata can likely survive better in short grass, its traditional range includes deserts (Nosek, 1973). Outside the UK H.punctata is also found in forest (Borşan et al, 2020). Whilst its established foci in the eastern Downs is relatively unwooded, if allowed to expand its range westward along the downland ridge (which was not certified by peer review) is the author/funder.…”
Section: Discussionmentioning
confidence: 99%